Extreme tachycardia complicating the use of disopyramide in atrial flutter. Issue 5 (November 1980) - Robertson, C E; Miller, H C
Abstract : A 59-year-old man presented with atrial flutter and a 2:1 atrioventricular response, which, after intravenous disopyramide, became 1:1. A mechanism of slowed atrial flutter rate and improved atrioventricular nodal conduction, similar to that recognised with quinidine, is suggested.